INTELLIGENT SYSTEM TO DETERMINE THE BEST LECTURER USING ADDITIVE RATIO ASSESSMENT ALGORITHM - Wahyudi Wahyudi; Budy Satria; Lutfil Khairi (LPPM Nusa Mandiri, 2025)
The quality of a lecturer's performance is one of the keys to institutional success that must be continuously improved. The performance assessment of lecturers in the Informatics study program of the Faculty of Information Technology, Andalas University faces obstacles in processing quantitative and qualitative data so that it is vulnerable to subjectivity including research productivity, teaching effectiveness, contributions to community service and additional activities. In addition, limitations in a systematic evaluation system result in unfairness and lack of transparency in the decision-making process. The research objective is to create a technology-based approach by applying the Additive Ratio Assessment method based on a Decision Support System. The ARAS method was chosen because it is able to determine effective final results based on multiple criteria that have been determined. The application of the ARAS method consists of 5 stages, namely determining the decision matrix, normalizing the decision matrix, weighting the normalization results, determining the optimum function value and ranking results. The results obtained are alternative data consisting of A1,A2,A3,A4,A5,A6,A7,A8,A9,A10,A11 and 8 criteria and weighting, namely the last education (10%), functional position (15%), certification (20%), number of publications (15%), author order (15%), publication index quality (10%), research grants (10%) and PkM (5%). The ranking results with the highest value in order 1-5 are 0.113875, 0.109785, 0.104235, 0.099005, 0.094715. The final conclusion of this research is that the ARAS method is able to prove the best lecturer assessment to be more efficient, transparent and subjective to be applied in the Andalas University Informatics study program.